Hardening Windows, Second Edition - Hassell, Jonathan (Apress, 2012)
This book is quick and simple, so it’s best to understand what’s inside before you even begin reading it. For one, the chapters themselves stand alone. You can read them in any order, and the material isn’t cumulative. Of course, you’re welcome to read them all, and cross-references are clearly identified when information in a chapter is discussed in more detail earlier in the book. However, if you choose to begin with Chapter 7, you won’t be missing anything. You also won’t be getting long, theoretical discussions about operating system design, kernel locking, OSI layers, and the like. Instead, you’re getting quick, practical, checklist-style suggestions with a minimum of fluff. This book is meant to be carried under your arm to client workstations, placed on the top of the server rack, or snugly kept right beside your monitor for easy reference. It certainly isn’t a 1,600-page Windows bible. Let me briefly address another issue: There are, of course, any number of hardening methods, and any number of opinions on how effective those methods are. This book would never be complete if it attempted to describe every view of every way to possibly secure a system from an unknown threat. Instead, I’ve chosen to keep the book short, using proven, time-tested ways to achieve maximum protection for the time and money invested. I think you’ll find the results more than acceptable.